Debata jako gatunek prasowy - Hodak, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
It is typical for civic, democratic societies to solve their problems by means of debate. Press offices often organize debates which are later transcribed and published in print. We can say that a debate has two dimensions: a real one and a press one. In order to appear in print, debates are first organized in a concrete place and time. In such conditions, the participants of a discussion are like actors performing in front of an audience. After the debate is published, they achieve greater popularity and attention. A press debate, just like other utilitarian texts, such as an invitation, is a parajournalistic genre. It is dialogue-based and persuasive. The participants often use emotional and language. The debate may exist in press in two formats, either as a kind of shorthand note or as a report. Both of these forms may co-exist within one text.